Development of an open-source virtual design framework for medical device development - Alam, Rahman (Cranfield University, 2009)
Economical and socio cultural changes have pressurised the health sector to become more sustainable. The sector is in need of a cultural change to bring more innovation in to new products and service developments. Diagnostic and therapeutic technologies need to be made available to the wider community. Allowing patients and clinicians to participate in the product development process has become essential; the current Intellectual Property model however does not accommodate this. Open source is an approach to designing, developing and delivering knowledge through the commitment and contribution of geographically dispersed individuals. Patents and other legislative property enforcements are unnecessary, making OS products free. Other benefits include the involvement of users from a wide range of backgrounds brining to the platform a spectrum of skills and specialist knowledge. The findings from this research detail the development of a generic concept creation model for medical device development in a virtual framework. Tools and techniques have been selected to ensure online collaborative development of the product is achieved through the concept creation stages. The biggest benefit of this research is the bridging between users and product developers in collaborative development. Limitations such as finding committed participants to continuously contribute through the concept creation process were also found.